(untitled) (Medico Legal Update, 2020)
Until now, cervical cancer is still as the leading cause of the death of women worldwide. WHO was estimates that cancer cases will rises sharply until 2030. Although the cervical cancer data of West Papua is the lowest 0.1% in Indonesia, especially in Sorong Raya region certainly wasn’t have the real data, but the iceberg phenomenon is still continues to occur. The study aim was to determine the effect of health education toward the early detection action of cervical cancer by the Maybrat’s Women. The research method used was quasi experimental with one group pretest posttest approach using non-probability puposive sampling technique. From the 30 participants were recruited based on inclusion criteria through the paired t test defined that there was an influence of health education toward early cervical cancer prevention action by Maybrat’s Women at Maybrat (p=0.011, ?<0.05). Health promotion of cervical cancer in Maybrat Regency should be strengthen by the adequately funding encouragrment.